2011
DOI: 10.1590/s0034-89102011005000023
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes do consumo de frutas e hortaliças em adolescentes por regressão quantílica

Abstract: OBJECTIVE:To analyze fruit and vegetable intake in adolescents and to identify associated factors. METHODS:A population-based cross-sectional study was conducted with a representative sample of 812 adolescents of both sexes in the city of São Paulo, Southeastern Brazil, in 2003. Food consumption was measured with the 24-hour dietary recall. Fruit and vegetable intake was described in percentiles. Quantile regression models were used to investigate the association between this intake and explanatory variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
4
13
0
5
Order By: Relevance
“…Prevalence under 30% has been reported in studies with teenagers independent of age and methods for evaluating consumption 7,9,17,18,19 . Two studies that evaluated 341 teenagers between 11 and 14 years in public schools in Curitiba 9 and 431 adolescents with an average of 12 years of age in public school of Piracicaba (SP) 20 , observed a prevalence of 29% and 28% of fruit consumption of more than 3 servings per day, respectively.…”
Section: Adolescencementioning
confidence: 99%
“…Prevalence under 30% has been reported in studies with teenagers independent of age and methods for evaluating consumption 7,9,17,18,19 . Two studies that evaluated 341 teenagers between 11 and 14 years in public schools in Curitiba 9 and 431 adolescents with an average of 12 years of age in public school of Piracicaba (SP) 20 , observed a prevalence of 29% and 28% of fruit consumption of more than 3 servings per day, respectively.…”
Section: Adolescencementioning
confidence: 99%
“…Studies are consistent on the grounds that food consciousness is related to environmental and family factors, besides state of motivation itself, and not to organic factors. 8,[10][11]17 Among these external factors, the association with living with parents and/or siblings was not expected either, since it is suggested that formal education and parental income, cohabitation time and family routine (not assessed in this analysis) are the major infl uential factors, rather than just the cohabitation characteristics. 14 The data reported in this analysis is useful for possible inferences about the population's eating habits, as poor awareness of food and nutrition refl ects on the consolidation of attitudes and food choices, even under interference from environmental factors hitherto mentioned.…”
Section: Discussionmentioning
confidence: 85%
“…[4][5][6][7] Prevalence of adequate consumption in adolescence, however, is reported as less than 30% in Brazil. 6,[8][9][10][11][12][13][14][15] Availability at home, exposure, family habits, formal education and income, media, school catering and awareness infl uence FV intake in adolescence. 2,8,10,11,14 At this age, one is capable of better absorbing the contents of interventions and managing food choices compared with children, and, in order to take effective action, it is important to assess the level of nutritional awareness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…a Adherence to the Food Guide recommendations is an important marker of the adequacy of the population's diet. With the exception of a few studies that evaluated consumption of fruit and vegetables and meat, 3,5 the percentages of the population with intake above or below the recommendations is not known, nor have subgroups at greater risk of deficiencies been identified.…”
mentioning
confidence: 99%